Spatial and Temporal High Processing of Visual and Auditory Stimuli in Cervical Dystonia - Chillemi, Gaetana; Calamuneri, Alessandro; Morgante, Francesca; Terranova, Carmen; Rizzo, Vincenzo; Girlanda, Paolo; Ghilardi, Maria Felice; Quartarone, Angelo (Frontiers in Neurology, 2017)
Objective: Investigation of spatial and temporal cognitive processing in Idiopathic Cervical Dystonia (CD) by means of specific tasks based on perception in time and space domains of visual and auditory stimuli. Background: Previous psychophysiological studies have investigated temporal and spatial characteristics of neural processing of sensory stimuli (mainly somatosensorial and visual), whereas the definition of such processing at higher cognitive level has not been sufficiently addressed. The impairment of time and space processing is likely driven by basal ganglia dysfunction. However, other cortical and subcortical areas, including cerebellum, may also be involved. Methods: We tested twenty-one subjects with Cervical Dystonia and twenty-two age-matched healthy controls with four recognition tasks exploring visuo-spatial, audio-spatial, visuo-temporal and audio-temporal processing. Dystonic subjects were subdivided in three groups according to the head movement pattern type (lateral: Laterocolis, rotation: Torticollis) as well as the presence of tremor (Tremor). Results: We found significant alteration of spatial processing in Laterocollis subgroup compared to controls, whereas impairment of temporal processing was observed in Torticollis subgroup compared to controls. Conclusions: Our results suggest that Dystonia is associated with a dysfunction of temporal and spatial processing for visual and auditory stimuli that could underlie the well-known abnormalities in sequence learning. Moreover, we suggest that different movement pattern type might lead to different dysfunctions at cognitive level within dystonic population.